HIF-1alpha Deficiency Attenuates the Cardiomyogenesis of Mouse Embryonic Stem Cells - Kudová, Jana; Procházková, Jiřina; Vašiček, Ondřej; Perečko, Tomáš; Sedláčková, Miroslava; Pešl, Martin; Pacherník, Jiří; Kubala, Lukáš (PloS one, 2016)
Cardiac cell formation, cardiomyogenesis, is critically dependent on oxygen availability. It is known that hypoxia, a reduced oxygen level, modulates the in vitro differentiation of pluripotent cells into cardiomyocytes via hypoxia inducible factor-1alpha (HIF-1α)-dependent mechanisms. However, the direct impact of HIF-1α deficiency on the formation and maturation of cardiac-like cells derived from mouse embryonic stem cells (mESC) in vitro remains to be elucidated. In the present study, we demonstrated that HIF-1α deficiency significantly altered the quality and quantity of mESC-derived cardiomyocytes. It was accompanied with lower mRNA and protein levels of cardiac cell specific markers (myosin heavy chains 6 and 7) and with a decreasing percentage of myosin heavy chain α and β, and cardiac troponin T-positive cells. As to structural aspects of the differentiated cardiomyocytes, the localization of contractile proteins (cardiac troponin T, myosin heavy chain α and β) and the organization of myofibrils were also different. Simultaneously, HIF-1α deficiency was associated with a lower percentage of beating embryoid bodies. Interestingly, an observed alteration in the in vitro differentiation scheme of HIF-1α deficient cells was accompanied with significantly lower expression of the endodermal marker (hepatic nuclear factor 4 alpha). These findings thus suggest that HIF-1α deficiency attenuates spontaneous cardiomyogenesis through the negative regulation of endoderm development in mESC differentiating in vitro.
Keywords: Actinin; Myosin Heavy Chains; Regeneration; hypoxie buňky; Oxygen; Muscle Development; lehké řetězce myosinu; srdce; myší embryonální kmenové buňky; Myosin Light Chains; Mouse Embryonic Stem Cells; Troponin T; buněčná diferenciace; faktor 1 indukovatelný hypoxií - podjednotka alfa; troponin T; stanovení celkové genové exprese; genový knockout; regenerace; vývoj svalů; Gene Expression Profiling; aktinin; kardiomyocyty; Animals; kyslík; Gene Knockout Techniques; Cell Hypoxia; zvířata; Myocytes, Cardiac; myši; Hypoxia-Inducible Factor 1, alpha Subunit; Heart; Mice; těžké řetězce myosinu; Cell Differentiation